2008
DOI: 10.1177/1065912908320931
|View full text |Cite
|
Sign up to set email alerts
|

Racial Threat, Residential Segregation, and the Policy Attitudes of Anglos

Abstract: The impact of racial context on the political behavior of Anglos has been a focus of social science research for well over half a century. We suggest that a shortcoming of earlier work has been the failure to account for the levels of segregation within a community. Relying on data from the Latino National Political Survey, our findings show that Anglo attitudes toward English-language and immigration policies are significantly related to changes in the size of the Latino population conditional on levels of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
150
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(156 citation statements)
references
References 30 publications
3
150
2
1
Order By: Relevance
“…Studies using contextual influences in municipalities, neighbourhoods and urban areas test both conflict and contact theories (e.g. Burns and Gimpel 2000;Rocha and Espino 2009) and find similar results as studies using countries and regions (Schlueter and Wagner 2008;Mirwaldt 2010). …”
Section: Empirical Findings: the Local Contextsupporting
confidence: 61%
“…Studies using contextual influences in municipalities, neighbourhoods and urban areas test both conflict and contact theories (e.g. Burns and Gimpel 2000;Rocha and Espino 2009) and find similar results as studies using countries and regions (Schlueter and Wagner 2008;Mirwaldt 2010). …”
Section: Empirical Findings: the Local Contextsupporting
confidence: 61%
“…784-785). Specifically, in regards to Latinos, Rocha and Espino have found that "increasing both the size of the Latino population and the level of residential segregation result in Anglos possessing less 'Latino-friendly' policy preferences" [62] (p. 423). Thus, two main components that scholars have used to measure perceived threat are group size and racial prejudice.…”
Section: Group Position Theorymentioning
confidence: 99%
“…However, in fact, much of Asians' success is due to selective migration and favorable immigration policy (62). Furthermore, the model minority frame obscures the income and educational heterogeneity of the Asian-American population (62).…”
Section: Group Position Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…From this item, we created a dichotomous variable, labeled Delay Welfare Benefits, and coded 1 for respondent's preferring the more restrictive position of making immigrants wait one year for benefits and 0 for those preferring to make immigrants immediately eligible for services. This item has been used in prior opinion research on immigration 32 and provides 28 Brader, Valentino and Suhay 2008;Campbell, Wong, and Citrin 2006;Hood and Morris 1997;Rocha and Espino 2009;Stein, Post, and Rinden 2000;Tolbert and Grummel 2003. 29 In addition to being consistent with prior research, extant research suggests that theoretical models other than those developed to explain national majority group reactions to immigrant minorities may be appropriate for explaining the dynamics of opinion on immigration among immigrants and other minority groups (e.g., Hainmueller and Hopkins 2014;Dancygier and Saunders 2006;Nteta 2013).…”
mentioning
confidence: 99%